PENGARUH ACAK EFEKTIVITAS PENGGUNAAN PERANGKAT MATEMATIKA AUGMENTED REALITY PADA MATERI BANGUN RUANG - Wijayanti, Rina; Rachmawati, Rachmawati (Universitas Insan Budi Utomo, 2021)
The challenge of learning is increasingly being felt in the era of a pandemic. This has been felt by the whole world since 2020 because of the Covid-19 virus. The online learning process is the effect of the WFH policy where students and teachers learn from home. Geometry is a study of material that is abstract in nature so that it requires projections of objects of space. This research is a development research which is followed by an experiment. Furthermore, the MAR is developed, namely Mathematics Augmented Reality. The material developed in MAR is a geometry according to the class V SD material, namely cubes, cuboid, prisms, pyramids, cones and spheres. The MAR equipment was tested in Kedung Pedaringan elementary school, the trial used a completely randomized design. A completely randomized design is the simplest type of experimental design. The results of the analysis concluded that the development of MAR learning tools for geometry for class V SD was proven statistically to have an effect on learning outcomes. The learning outcomes of students are increased and homogen.